Incidencia del síndrome diarreico agudo por rotavirus en menores de 1 a 6 meses hospitalizados en el área de pediatría Hospital Teófilo Dávila entre el 1 de Junio al 30 de Septiembre del año 2014. - Alvear Gálvez, Oswaldo Estuardo (2016)
Acute diarrhea is one of the most important public health problems today mainly in developing countries, particularly in Ecuador, where the disease is a major cause of infant morbidity.